Transarterial Chemoembolization Combined with Sorafenib in Patients with BCLC Stage C Hepatocellular Carcinoma - Liu KC; Hao YH; Lv WF; Jia WD; Ji CS; Zhou CZ; Cheng DL; Xu SB; Gao ZG; Su MX; Shi CS (Dove Medical Press, 2020)
Kai-Cai Liu,1,* Ying-Hong Hao,2,* Wei-Fu Lv,2 Wei-Dong Jia,3 Chu-Shu Ji,4 Chun-Ze Zhou,2 De-Lei Cheng,2 Shao-Bao Xu,1 Zong-Gen Gao,1 Ming-Xue Su,1 Chang-Sheng Shi1 1Infection Hospital, Anhui Provincial Hospital, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei 230000, People’s Republic of China; 2Department of Radiology, The First Affiliated Hospital of USTC, Anhui Provincial Hospital, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, Anhui 230022, People’s Republic of China; 3Department of General Surgery, The First Affiliated Hospital of USTC, Anhui Provincial Hospital, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, Anhui 230022, People’s Republic of China; 4Medical Oncology, The First Affiliated Hospital of USTC, Anhui Provincial Hospital, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, Anhui 230022, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei-Fu LvDepartment of Radiology, The First Affiliated Hospital of USTC, Anhui Provincial Hospital, Division of Life Sciences and Medicine, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, Anhui 230022, People’s Republic of ChinaTel/ Fax +86 551 6228 3139Email weifulv@ustc.edu.cnPurpose: Transcatheter arterial chemoembolization (TACE) and targeted therapy have become common methods in the treatment of advanced hepatocellular carcinoma (HCC). The purpose of this study was to evaluate the safety and efficacy of TACE combined with sorafenib (TACE-sorafenib) and TACE alone for the treatment of Barcelona clinical stage C HCC.Methods: The clinical data of 75 patients with BCLC stage C HCC who received TACE-sorafenib or TACE as the initial treatment were retrospectively analyzed. Tumor response, time to progression (TTP), overall survival (OS), and adverse events were compared at 1 month after surgery in the two groups.Results: One month after treatment, the disease control rate in the TACE-sorafenib group was higher than that in the TACE group alone (82.76% and 57.50%, respectively, P = 0.018). The median values of TTP and OS in the TACE-sorafenib group were longer than those in the TACE group (TTP was 7.6 and 3.4 months, respectively, P = 0.002; OS was 13.6 and 6.3 months, respectively, P = 0.041). The cumulative survival time at 3 months, 6 months, and 1 year was higher in the TACE-sorafenib group than in the TACE group (83.5%, 71.2%, 45.7% vs 57.4%, 40.6%, 21.2%). Sorafenib-related side effects such as hypertension, hand-foot syndrome, and oral ulcers were more common than those in the TACE group alone (P< 0.05).Conclusion: Compared with TACE treatment alone, TACE combined with sorafenib in BCLC-C stage HCC significantly improved disease control rate, TTP, and OS, and no significant increase in adverse reactions was observed.Keywords: hepatocellular carcinoma, TACE, sorafenib, survival